Um bê-a-bá de ordem e progresso: educação social e instrução escolar no Ceará dos anos 1940. - Silva, Manuelle Araújo da (2017)
In January 1944, the popular morning newspaper Gazeta de Notícias published the first issue of the column entitled Ensino e Educação (Teaching and Education), signed by Coelho Sampaio. With irregular frequency, but being, as a rule, weekly, this section lasted until January of 1950. This column stands out because it is a fixed journalistic space, destined to reflect on educational matters of that time, in the form of teachings or systematizations of steps to be taken in order to achieve the improvement of Education, evaluating the aggrandizement of the Nation as a correlate. This research aims to understand, from a case study of the column named Ensino e Educação (Teaching and Education), written by Coelho Sampaio in the newspaper Gazeta de Notícias from Ceará, from 1944 to 1950, how speeches about school education and a social education based on moralizing and disciplining ideals under the aegis of the country's progress are articulated. In order to do so, we investigated latent educational problems of the period, such as: what could mean the ideal of moralizing customs, as an educational task? What sustained the desire to sanitize reading acitivities and means of communication? How were the function and the teaching field in the period idealized? What are the constructions around the notion of childhood and student? What are the foundations of the ideals of education for work, in a context of industrialization and urbanization? In what way has this influenced discourses aimed at professional, rural and adult education? The journalistic sources are the main ones in this study, but it is drawn a parallel with other types of documents: official ones, produced by the Ministry of Education and Health, and the Department of Education of Ceará; periodical sources, such as Revista Brasileira de Estudos Pedagogicos (Brazilian Journal of Pedagogical Studies - RBEP), Almanaque do Estado do Ceará (the Almanac of the State of Ceará) and Censo Demográfico do Ceará (the Demographic Census of Ceará); didactic literature; as well as biographical and memorialistic sources. As far as methodological aspects are concerned, the concept of scale games, outlined by Jacques Revel, is used to investigate the relationships between social and educational aspects, varying the angles of analysis between "micro" and "macro" approaches. As a conclusion, it should be noted that the pair of concepts of Education and Social Education are shown to be more central than the pair of concepts of Teaching and School Instruction, as they generate other concepts linked to the notions of morality, civility and order, although in the present research those both pairs of concepts are somehow connected.